2017
DOI: 10.4103/2045-9912.208515
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hydrogen rich water on the intestinal ischemia/reperfusion injury due to intestinal intussusception in a rat model

Abstract: This study aimed to investigate the protective effects of hydrogen rich water on the intestinal ischemia/reperfusion (I/R) injury in a rat intestinal intussusception (II) model. Ninety Sprague-Dawley rats were randomly assigned into three groups (n = 30 per group). In sham group, rats received laparotomy, and the intestine was exposed for 15 minutes without II. In I/R + saline group and I/R + hydrogen group, rats received II after laparotomy and then intestine was relocated 8 hours later, followed by immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…In mapping all targeted genes to the KEGG database, we noted that they participated in the following: "AMPK signaling pathway", "FoxO signaling pathway", "Cellular senescence", "Relaxin signaling pathway", "RAS pathway", "Protein procession", "Signaling pathways regulating pluripotency of stem cells" and "Taurine and hypotaurine metabolism". This is consistent with ndings in the literature that these signaling pathways play important roles in I/R [17][18][19][20][21][22]. However, the involvement of these dysregulated tRFs and their target genes in I/R in the pediatric intussusception process via these signaling pathways require further studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In mapping all targeted genes to the KEGG database, we noted that they participated in the following: "AMPK signaling pathway", "FoxO signaling pathway", "Cellular senescence", "Relaxin signaling pathway", "RAS pathway", "Protein procession", "Signaling pathways regulating pluripotency of stem cells" and "Taurine and hypotaurine metabolism". This is consistent with ndings in the literature that these signaling pathways play important roles in I/R [17][18][19][20][21][22]. However, the involvement of these dysregulated tRFs and their target genes in I/R in the pediatric intussusception process via these signaling pathways require further studies.…”
Section: Discussionsupporting
confidence: 91%
“…I/R in intussusception can result in mucosal erosion and hemorrhagic ulceration, as well as necrosis of the bowel, lung injury, and multiple-organ dysfunction syndrome [20]. Oxidative stress can play a crucial role in I/R in pediatric intussusception [21]. Early detection of intestinal I/R in intussusception can improve prognosis and reduce complications in the intestines and extraintestinal organs.…”
Section: Discussionmentioning
confidence: 99%
“…For oxidative stress not only exaggerates host inflammatory response to I/R, but also damages cellular components indiscriminately, leading to escalated cellular apoptosis and thus tissue deterioration [5]. In line with previous studies [3,9], we demonstrated advanced disruption of intestinal mucosa in mice subjected to I/R, evidenced by massive apoptosis of epithelial cells and lifting of epithelium down the villi. However, mice pretreated with HRS exhibited significantly lower level of epithelial apoptosis and preserved tissue integrity in the intestine mucosa.…”
Section: Discussionsupporting
confidence: 89%
“…Saline saturated with hydrogen, a proven antioxidant, has been shown to protect tissue by antioxidation and anti-inflammation in clinic [5], as well as in various animal models of I/R [6,7], including intestinal I/R [8]. Such hydrogen-rich saline (HRS), by selectively reacting with hydroxyl radicals and peroxynitrite, the most toxics of ROS, can effectively reduce cellular oxidative stress and apoptosis [6,9]. Administration of HRS prior to intestinal I/R has been shown to suppress lipid oxidation, proinflammatory cytokines, and crypt cell apoptosis in intestinal mucosa, conferring significant protection of the intestine [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that hydrogen exerts antioxidant, anti-inflammatory, and anti-apoptotic properties. For instance, hydrogen can mitigate ischemia/reperfusion injury of kidney (Cardinal et al, 2010) and intestine (Wu et al, 2017). Hydrogen enriched saline can attenuate neuronal apoptosis and oxidative stress post SAH (Hong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%